THE EFFECT OF SERVICE QUALITY, BRAND IMAGE, AND PRICE PERCEPTION ON CUSTOMER SATISFACTION ON J&T BATUPHAT COURIER SERVICES IN LHOKSEUMAWE CITY - Fathul Rezki Iradha; T. Edyansyah; Adnan; Rusydi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research aims to determine the influence of service quality, brand image and price perception on customer satisfaction at the J&T Batuphat courier service, Lhokseumawe City. The data in this research was collected through a survey method using a questionnaire as a data collection instrument. The sample in this study was 100 J&T Express Batuphat service users in Lhokseumawe City using a purposive sampling technique. This research uses a quantitative approach with linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. Hypothesis, coefficients are determined using the SPSS version 25.0 program. The results of the research show that partially price perception has no significant effect on consumer satisfaction with the J&T Batuphat courier service in Lhokseumawe City, while service quality and brand image have a positive and significant effect on consumer satisfaction with the J&T Batuphat courier service in Lhokseumawe City. Lhokseumawe City. Simultaneously, service quality, brand image and price perception have a positive and significant effect on customer satisfaction at the J&T Batuphat courier service, Lhokseumawe City. The Adjusted R Square value of 0.631 obtained by this variable can be explained by the independent variables, namely service quality, brand image and price perception, which is 63.1%, while the remaining 36.9% can be explained by other variables not analyzed in this research.